Some shallow water octocorals (Coelenterata: Anthozoa) of the Persian Gulf - Samimi-Namin, K.; van Ofwegen, L. P. (Zootaxa, 2009)
A collection of octocorals from the Persian Gulf is examined, and all species are identified to at least genus level. Sinularia erecta Tixier-Durivault, 1945; S. compressa Tixier-Durivault, 1945; Subergorgia suberosa (Pallas, 1766); Junceella juncea (Pallas, 1766); and Acanthogorgia spinosa Hiles, 1899, could be identified further. With some doubts Trimuricea reticulata (Thomson & Simpson, 1909), Menella cf. kanisa Grasshoff, 2000, and Verrucella cf. reticulata (Thomson & Simpson, 1909) are tentatively identified. Subergorgia perezi Stiasny, 1940 is synonymised with Subergorgia suberosa (Pallas, 1766), and Echinogorgia bahrelfarsi Stiasny, 1940 is assigned to Menella. Three new species are described and depicted.